2014
DOI: 10.5897/ajb2013.12115
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of heavy metals by agroforestry waste derived activated carbons applied to aqueous solutions

Abstract: Activated carbons prepared from macadamia nut shells, baobab shells, pigeon pea husks, rice husks, Moringa oleifera husks, and marula stones were investigated for their abilities to adsorb Pb(II), Zn(II), Cu(II), Ni(II), Fe(II), Mn(II), Hg(II), Cr(III), As(III) and Cd(II) from aqueous solutions. Batch adsorption experiments were conducted at pH values of 4, 5 and 6. Metal ion adsorption generally increased as the pH was increased from 4 to 6. Percentage adsorption values were above 60% for adsorption of Hg(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Biosorption has gained more research interests because it is renewable and cheap and marula shells have gained interest in reducing quantity of Pb (II) and Cu (II) Moyo et al (2015), methylene blue in aqueous solution (Mathew et al, 2017;, adsorption of methyl orange and zinc Lotfy et al (2012), removal of parasites Misihairabgwi et al (2014). Marula shells can be acid activated resulting in increase in acidic functional groups.…”
Section: Adsorption In Oilsmentioning
confidence: 99%
“…Biosorption has gained more research interests because it is renewable and cheap and marula shells have gained interest in reducing quantity of Pb (II) and Cu (II) Moyo et al (2015), methylene blue in aqueous solution (Mathew et al, 2017;, adsorption of methyl orange and zinc Lotfy et al (2012), removal of parasites Misihairabgwi et al (2014). Marula shells can be acid activated resulting in increase in acidic functional groups.…”
Section: Adsorption In Oilsmentioning
confidence: 99%
“…[14] stated that adsorption sites at equilibrium are saturated; therefore cannot adsorb any more of the metal ions. [15] reported that removal of Cr (VI) ions from aqueous solution using activated carbon increased with contact time and obtained a saturation point at 90 minutes.…”
Section: Effect Of Equilibration Time and Initial Concentration On Admentioning
confidence: 99%